Enforcement of Law Against Modified Two-Wheeled Vehicle Users: A Case Study of the Central Aceh Resort Police - Ferdian, Hendra; Astini, Dewi; Fazzan, Fazzan (Yayasan Abdurrauf Cendekia Nusantara, 2025)
This research is motivated by the increasing use of racing exhausts on motorcycles in Central Aceh Regency, which do not comply with safety and environmental standards. Such modifications not only cause noise disturbances but also violate legal provisions stipulated in Law Number 22 of 2009 on Road Traffic and Transportation, Article 48 Paragraph (3), and the Minister of Environment Regulation Number 07 of 2009 concerning Noise Limits for Motor Vehicles. The purpose of this study is to examine the law enforcement carried out by the Central Aceh Police against modified motorcycles, to identify the obstacles faced in the enforcement process, and to analyze the efforts made to overcome these challenges. The study applies an empirical juridical method with a case study approach, using both primary and secondary data, analyzed qualitatively based on empirical findings in the field. The results indicate that law enforcement encounters both internal and external obstacles. Internal obstacles are related to the effectiveness of the police in supervising and enforcing the law against vehicle modifications. External obstacles are influenced by social factors, particularly the growing trend of vehicle modifications shaped by external cultural influences. The internal efforts undertaken include strengthening the role of the police and enhancing public legal awareness. Meanwhile, external efforts focus on limiting the impact of modification trends from outside the region to prevent their spread within the community. This study recommends that the people of Central Aceh avoid using modified vehicles, and that the police increase patrol frequency and implement strict sanctions, including fines, to reduce such violations.